Seasonal Niche Partitioning of Surface Temperate Open Ocean Prokaryotic Communities - Mena, Catalina; Reglero, Patricia; Balbín, Rosa; Martín, Melissa; Santiago, Rocío; Sintes, Eva (Frontiers in Microbiology, 2020)
Surface microbial communities are exposed to seasonally changing environmental conditions, resulting in recurring patterns of community composition. However, knowledge on temporal dynamics of open ocean microbial communities remains scarce. Seasonal patterns and associations of taxa and oligotypes from surface and chlorophyll maximum layers in the western Mediterranean Sea were studied over a two-year period. Summer stratification vs. winter mixing governed not only the prokaryotic community composition and diversity but also the temporal dynamics and co-occurrence association networks of oligotypes. Flavobacteriales, Rhodobacterales, SAR11, SAR86 and Synechococcales oligotypes exhibited contrasting seasonal dynamics, and consequently, specific microbial assemblages and potential inter-oligotype connections characterized the different seasons. In addition, oligotypes composition and dynamics differed between surface and deep chlorophyll maximum prokaryotic communities, indicating depth-related environmental gradients as a major factor affecting association networks between closely related taxa. Taken together, the seasonal and depth specialization of oligotypes suggest temporal dynamics of community composition and metabolism, influencing ecosystem function and global biogeochemical cycles. Moreover, our results indicate highly specific associations between microbes, pointing to keystone ecotypes and fine tuning of the microbe’s realized niche.